Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The global economy has entered a dangerous new phase with severe downside risks. The Fund has been called by the IMFC to contribute to an orderly resolution of these tensions, and the membership must be prepared for bold action. Our first responsibility is to help develop and coordinate solutions to immediate threats to global stability, in particular to provide insightful analysis and policy advice to address fiscalfinancial vulnerabilities and rekindle growth and job creation. Yet we must also be prepared to fortify the global financial safety net. Secondly, we must redouble efforts to make the international monetary system (IMS) stronger in the longer term-through more effective surveillance and a clearer shared vision of the system's key underpinnings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet